2003
DOI: 10.1135/cccc20032055
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of Catalysis by Carboxypeptidase A: Could Gas-Phase Calculations Support a Mechanism?

Abstract: We compare recent quantum mechanical computations of alternative reaction pathways for carboxypeptidase A, a zinc proteinase, in an "enzyme environment" to similar calculations in the "gas phase" that include the minimal chemical entities that are required for a non-catalytic reaction. The main question that we address is whether anything may be learned from such reduced representations. Two general acid-general base alternative pathways and one nucleophilic pathway are compared. The original calculations were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
1
0
Order By: Relevance
“…Goldblum and co-workers performed a semi-empirical QM study on the alternative mechanisms for zinc proteinases 5860. Their results suggest that the anhydride pathway is not a viable candidate to be the mechanism of cleavage of peptides by CPA 60 and that both GAGB mechanisms are feasible 58,59. Banci et al 61 demonstrated the mobility of Arg127 and Tyr248 and suggested 62 that both “nucleophilic” and “water-promoted” pathways are structurally feasible, although the water-promoted mechanism is favored energetically.…”
Section: Introductionmentioning
confidence: 99%
“…Goldblum and co-workers performed a semi-empirical QM study on the alternative mechanisms for zinc proteinases 5860. Their results suggest that the anhydride pathway is not a viable candidate to be the mechanism of cleavage of peptides by CPA 60 and that both GAGB mechanisms are feasible 58,59. Banci et al 61 demonstrated the mobility of Arg127 and Tyr248 and suggested 62 that both “nucleophilic” and “water-promoted” pathways are structurally feasible, although the water-promoted mechanism is favored energetically.…”
Section: Introductionmentioning
confidence: 99%